Visum Et Repertum in the Evidencing Process of Rape in Indonesia - Arief Budiono1, Wilma Silalahi2, Ayesha Hendriana Ngestiningrum3, Wafda Vivid Izziyana1, Suparji4, S (Institute of Medico-legal Publications Pvt Ltd, 2020)
Rape is part of sexual crime in which its evidencing process is rather complicated if the victims do not directly report the case, or if the law-enforcing apparatus are not quick in handling it. Visum et repertum is a medical-aspect report from the doctor after a written demand from the law-enforcing apparatus of authority for the sake of the case investigation and examination in court. Thus, from this definition, visum et repertum can only be proposed by the law enforcers or the authorities such as the police department, the lawyers, or the judges in court to the special doctors who are in charge of that field. The lawyers and the judges may ask for the visum through the police department. This research uses a normative doctrinal method. The research results show that the evidencing process of rape as a criminal act of sexual crime has some different difficulties compared to other general criminal acts. This is because there needs to be visum et repertum which will uncover the perpetrator and the time of occurrence, which will ease the process of searching for and finding the perpetrator. The obstacle of visum et repertum is that its evidencing process is the same as a letter of evidence in the aspect of power.